A SYSTEM OF TRAINING TEACHERS FOR WORK WITH CHILDREN WITH DISABILITIES IN THE CONTEXT OF INCLUSIVE EDUCATION - Artsimovich , Irina; Dokhoyan, Anna; Maslova, Irina; Oleshko, Tatiana; Skiba, Natalya (Revista Inclusiones, 2020)
The article represents the analysis of scientific research on a given problem; an author’s model of a system of training teachers for work with children with disabilities in the context of inclusive education is provided by the example of teaching psychological disciplines in Armavir State Pedagogical University. A model of psychological training for future teachers, including in the framework of inclusive education, is presented. The authors note the shortcomings of inclusive education, in particular the lack of public readiness for the acceptance of a person with disabilities, the imperfection of the system of social support and provision of such persons and disabled people, the professional failure of teachers to work with this contingent of students.